jFakih: Modelling mobile learning game - Hussain, Azham; Abdul Mutalib, Norasyikin; Yasin, Azman (2014)
This study introduce a new method for learning Jawi for deaf children by adding some hand signs and named the method as jFakih.Since Fakih is a learning method for deaf children to read Quran, it's also possible to be used in Jawi learning for deaf children.Fakih used number and colours to recognize the Arabic character and also the script. We also designed the reference model for jFakih for future development of mobile application.By using waterfall-agile hybrid method, we gathered the requirements and designed the model using UML technique.The model was validated through prototype development and some survey was implemented to get feedbacks from users.